IMF programs and tax effort What role for institutions in Africa? - (:unkn) unknown (My University, 2011)
When compared to other developing countries, most Sub-Saharan African countries are characterized by a disappointing level of development. Among the factors explaining this poor performance, the inadequate supply of public goods is often advocated. This inadequate supply is due either to poor efficiency of public expenditure, or to an insufficient tax effort. This paper is focused on this last factor. One of the reasons for the low level of public revenues could be the weak impact of the IMF programs on the tax effort. In the agreements that developing countries reach with the IMF, they commit to reduce their macro-economic imbalances, notably fiscal deficit, to a sustainable level. The measures necessary to achieve the overall budgetary objectives apply mainly to public expenditures as they are easy to reduce in the short term. However, the hypothesis of a positive effect of IMF programs must be considered: one objective of the African governments could be to maintain public expenditures at their previous level. To this end, African governments could choose to mobilize additional public revenues. Thus, most of IMF programs promote tax reforms leading to a more effective policy of public revenue mobilization. This last scenario of an increase of the level of public revenue is corroborated by the econometric analysis. The level of public revenue depends, among other factors, on the quality of institutions. However, the institutional quality of custom and tax administrations is weaker in Africa than elsewhere. This poor quality reduces the efficiency of IMF programs which may have a lower impact on the level of public revenue in African countries. These results point up two main lessons for the IMF (and more generally for lenders) and for recipient countries: 1) The role of technical assistance associated with the IMF programs is crucial, since it enables capacity reinforcement of the technical administrations in charge of the definition and implementati
Keywords: African Research